Creative Universities : Reimagining Education for Global Challenges and Alternative Futures (2021) - Anne-Marie Smith (PRISM)
The book ‘Creative Universities’ by Anke Schwittay (2021) is unlike any other academic text I have read about teaching; the pages buzz with hope, creative vision and radical possibilities, and it left me wanting to do my teaching differently, to shake up our learning spaces, and to keep asking questions. This book is a call to arms in which Schwittay invites us to have courage, take risks, cause disturbance, be creative, and alongside our students reshape the way we engage in education via a critical-creative pedagogy (hereafter C-CP). The words and ideas laid on the pages nudge us into reflections about our identity as academics, asking us difficult questions: how courageous can we be? What risks are we willing to take?